PREVALENCE OF OVERWEIGHT AND OBESITY IN MEMBERS OF TWO LARGE FITNESS CLUBS OF THE CITY OF RIO DE JANEIRO, RJ, BRAZIL - Tony Meireles Santos; Bruno Ribeiro Ramalho Oliveira; Geraldo de Albuquerque Maranhão Neto; Marcos Santos Ferreira; Walter Rolph Thompson (Revista Brasileira de Atividade Física e Saúde)
The objectives of this study were: to assess the prevalence of overweight/obesity in two large fitness clubs of the city of Rio de Janeiro, Brazil; to compare its results with municipal andnational demographic data; and to compare the prevalence and magnitude of overweight/obesity between genders and age groups. A cross-sectional, retrospective study wasconducted with 12,415 subjects (4,932 men and 7,483 women), selected from the database of two fitness clubs of the city of Rio de Janeiro. After age categorization by decade (20-29, 30-39, 40-49, 50-59, 60-69 and ≥ 70 years) and body mass index (BMI) classifi cation (underweightand normal weight: < 25 kg/m2, and overweight: ≥ 25 kg/m2), prevalences were compared to municipal and national data. In addition, a comparison of the prevalence and magnitude of overweight was made between genders and age groups. The prevalence of overweight was higher in men, regardless of age group. Comparing the results with municipal and national data, BMI values were significantly higher (p≤0.01) in men (7.7%) and lower in women (21.6%). The two-way analysis of variance (age and gender) found lower values in women (21.4±1.8kg/m2), when compared to men (22.6±1.8 kg/m2) in the underweight and normal weightcategories, but not in the overweight category (28,1±3,1 versus 28,2±3,0 kg/m2, for women and men respectively). Women showed a 3-fold lower prevalence of overweight in the 20 to 49 year age group, which became similar to that of men after the age of 50 years. New studies are needed to confirm these fi ndings or to identify regional and socioeconomic influences.